2015
DOI: 10.1007/8904_2015_481
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolinemia in Type 2 Glutaric Aciduria and MADD-Like Profiles

Abstract: Classical neonatal-onset glutaric aciduria type 2 (MAD deficiency) is a severe disorder of mitochondrial fatty acid oxidation associated with poor survival. Secondary dysfunction of acyl-CoA dehydrogenases may result from deficiency for riboflavin transporters, leading to severe disorders that, nevertheless, are treatable by riboflavin supplementation. In the last 10 years, we identified nine newborns with biochemical features consistent with MAD deficiency, only four of whom survived past the neonatal period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In pregnancy, it is passed from the mother to the child via the placenta probably using the riboflavin transporter RFVT1 ( SLC52A1 ) 26 . Transient MADD‐like biochemical profiles have been reported previously in healthy infants of whom the mothers were (suspected to be) riboflavin deficient during pregnancy 15,16,27 . Medical history taking of the infants' mothers described in our case report revealed that all of them either followed an imbalanced or lactose‐free diet or were (temporarily) vegan or vegetarian during pregnancy.…”
Section: Discussionsupporting
confidence: 53%
“…In pregnancy, it is passed from the mother to the child via the placenta probably using the riboflavin transporter RFVT1 ( SLC52A1 ) 26 . Transient MADD‐like biochemical profiles have been reported previously in healthy infants of whom the mothers were (suspected to be) riboflavin deficient during pregnancy 15,16,27 . Medical history taking of the infants' mothers described in our case report revealed that all of them either followed an imbalanced or lactose‐free diet or were (temporarily) vegan or vegetarian during pregnancy.…”
Section: Discussionsupporting
confidence: 53%
“…In the AM group, the levels of His, Phe, Thr, Glu, Met, and Gly were all abnormal. Abnormalities of single amino acids in circulating blood are closely related to the prevalence of diseases such as histidinemia (Rojas et al, 2012 ), hyperphenylalaninemia and hyperprolinemia (Pontoizeau et al, 2016 ), as well as other amino-acid-related metabolic diseases. These results suggest that the amino acid composition in the hyperproteinemic silkworm FBs were altered, implying that they have adverse effects on tissues and their related functions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, another supporting evidence of FAD scarcity in this patient is the hyperprolinemia we detected at the time of first decompensation, consistent with a mitochondrial flavoenzyme proline dehydrogenase deficiency. 51 Indeed, an alimentary maternal Rf deficiency has been described in other infants as responsible for transient and moderate VLCAD deficiency. 52…”
Section: Discussionmentioning
confidence: 99%